2017
DOI: 10.1002/bse.1977
|View full text |Cite
|
Sign up to set email alerts
|

Green Product Development and Product Portfolio Management: Empirical Evidence from an Emerging Economy

Abstract: Few studies have explored the relationship between green products development (GPD) and product portfolio management (PPM). When considering evidence from emerging economies, the knowledge gap is even deeper. Consequently, the objective of this work is to analyze how green and traditional practices of new product development (NPD) influence product portfolio and NPD performance. In addition, we explore how GPD opens new markets and technology opportunities. The empirical evidence is based on a sample of firms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 91 publications
(178 reference statements)
0
22
0
10
Order By: Relevance
“…The regression analysis proved that MER has significant negative effect on innovation efficiency. The result is surprising that diverse literature pointed out the benefits of reducing material and energy consumption, such as increasing competitive advantage, profitability, and firm performance [7][8][9][10][11][12][13]. Given that the literatures consider outputs only, however, this study does not contradict the previous studies but rather indicate the possibility that input used for innovation might overweigh the output yielded.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…The regression analysis proved that MER has significant negative effect on innovation efficiency. The result is surprising that diverse literature pointed out the benefits of reducing material and energy consumption, such as increasing competitive advantage, profitability, and firm performance [7][8][9][10][11][12][13]. Given that the literatures consider outputs only, however, this study does not contradict the previous studies but rather indicate the possibility that input used for innovation might overweigh the output yielded.…”
Section: Resultsmentioning
confidence: 51%
“…González-Moreno et al [12] also pointed out that environmental oriented innovation affects positively to manufacturing process and logistics. Jugend et al [13] found that green product development is positively correlated with product portfolio performance and creation of new opportunities.…”
Section: Materials and Energy Reduction And Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…A gestão do portfólio é ainda mais relevante por acontecer nos estágios iniciais do desenvolvimento de novos produtos (Jugend et al, 2017), tornando-se crucial para o sucesso do produto (Kester, Hultink & Griffin, 2014) e para a diminuição do tempo de lançamento no mercado (Jacobs & Swink, 2011), e representando uma grande oportunidade de redução do impacto ambiental no desenvolvimento de produtos (Collado-Ruiz & Ostad- Ahmad-Ghorabi, 2013;Sihvonen & Partanen, 2016).…”
Section: Contextualização E Delimitação Do Temaunclassified
“…Sem nenhuma intenção de comparação, pois trata-se de assuntos distintos, esta tese limitou-se ao item um dessa metodologia, assim como a maioria dos tratados em economia, que lidam com esse nível de abstração.Por fim, é necessário destacar que a complexidade na gestão de PPDNP é dinâmica e deve agregar outros fatores ou preocupações que tornarão o tema ainda mais complexo. Exemplo disso, vem de autores como Davoudpour, Rezaee e Ashrafi (2012), Vandaele e Decouttere (2013),Jugend et al (2017), que trazem para o nível…”
unclassified